2019
DOI: 10.1021/acs.energyfuels.8b04208
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Sub-micrometer Ash Formation from Pulverized Biomass Combustion with Ash Composition

Abstract: The present work investigated the relationship of sub-micrometer ash (inorganic particulate matter with an aerodynamic diameter of <1 μm, PM1) formation from pulverized biomass combustion with fuel ash composition. PM1 yields from burning pulverized biomasses under similar experimental conditions, together with ash composition of the parent fuels, were gathered from the literature. The correlations between the PM1 yield and the indexes related to ash composition were evaluated using linear regression analysis.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…Figures and ). In addition, (4) other pollutants such as NO x , SO x , , particulate matter, , volatile organic compounds (VOC), inorganics, and metals and metalloids are emitted after combustion. Thus, it is strongly preferable to avoid an unneeded simple combustion and to valorize the combustion technology even if renewable biomass fuel is used.…”
Section: Characterization Of Combustion Technologymentioning
confidence: 99%
“…Figures and ). In addition, (4) other pollutants such as NO x , SO x , , particulate matter, , volatile organic compounds (VOC), inorganics, and metals and metalloids are emitted after combustion. Thus, it is strongly preferable to avoid an unneeded simple combustion and to valorize the combustion technology even if renewable biomass fuel is used.…”
Section: Characterization Of Combustion Technologymentioning
confidence: 99%
“…A challenge in burning biomass in PF boilers is its content of alkali metals. Higher alkali contents might lead to increased ash deposition and aerosol formation . Gaseous alkali salts from biomass combustion are transferred with the flue gas and deposited on boiler surfaces, accelerating corrosion and deactivation of the SCR catalyst. The use of fuel additives is a promising technique to solve this problem in PF boilers .…”
Section: Introductionmentioning
confidence: 99%
“…In solid fuel combustion, the ultrafine PM 0.1 or PM 0.2 emission (denoting the aerodynamic diameter less than 0.1 or 0.2 μm) is extremely hazardous due to the enrichment of toxic species. Even worse, the ultrafine fraction is more likely to escape from the dust removal devices . Extensive research efforts have been devoted to understanding the ultrafine PM formation and revealed a vaporization-nucleation pathway. It was reported that, compared with bituminous coal, the low-rank lignite is more prone to generate PM 0.2 which is dominant by the alkali and alkaline earth metallic (AAEM) elements. , Likewise, ultrafine PM from burning biomass and sewage sludge is composed of fuel-dependent volatilized mineral species containing alkali (Na and K), S, Cl, and P. Nevertheless, it remains a challenge to predict ultrafine PM yields in practical combustors due to the complex interactions of multiple species.…”
Section: Introductionmentioning
confidence: 99%